Online-Based Public Service Innovation at the Makassar City Civil Registry Office - Devi, Sri devi; Madani, Muhlis; Mustari, Nuryanti; Fatmawati, Fatmawati (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The goal of this study is to describe and evaluate how the Makassar City Civil Registry Office has improved public service. Data was gathered through observation, interviews, and documentation approaches as part of a descriptive qualitative methodology. There were seven witnesses from Makassar City's Department of Population and Civil Registry. Data analysis involves gathering data, reducing it, presenting it, confirming it, and drawing conclusions. triangulation-based data validation. The study's findings demonstrate that, first, changes in service activities have been driven by novelty, the impact of COVID-19 on Makassar City, and the government's social restriction policies, with a technology approach to support online services. Second, productivity at Dukcapil Makassar City through online service activities, each apparatus has been directed and supervised in order to maximize the service tasks it can perform for the community using technology. Third, effective online services at the Makassar City dukcapil can encourage community service projects and limit the spread of Covid-19. The drawback is that it is susceptible to information leaks and the community is still having trouble adjusting to new service trajectories. Fourth, Sustainable, in an effort to assist the Makassar City government's ambition of turning the city into a smart city, the population and civil registration service has established a strategy to enhance online services.